Fluorescein sodium in the surgical treatment of pleomorphic xanthoastrocytomas: Results from a retrospective study - Falco, Jacopo; Broggi, Morgan; Vetrano, Ignazio G.; Rubiu, Emanuele; Schiariti, Marco; Restelli, Francesco; Mazzapicchi, Elio; Bonomo, Giulio; La Corte, Emanuele; Ferroli, Paolo; Acerbi, Francesco (Frontiers in Oncology, 2022)
Objective Pleomorphic xanthoastrocytoma (PXA) is a rare brain tumor, most commonly affecting children and young adults. Surgical resection represents the mainstay of treatment, and extent of resection is associated with improved survival. In this study, we analyzed the role of sodium fluorescein (SF) in improving intraoperative visualization easing resection. Methods Surgical database of FLUOCERTUM study (Besta Institute, Milan, Italy) was retrospectively reviewed to find pleomorphic xanthoastrocytomas and anaplastic xanthoastrocytomas, according to WHO-2016/2021 classification, surgically removed by a fluorescein-guided technique from March 2016 to February 2022. SF was intravenously injected (5mg/kg) immediately after induction of general anesthesia. Tumors were removed using a microsurgical technique with the YELLOW 560 filter (Carl Zeiss Meditec, Oberkochen, Germany). Results Twelve patients (7 males and 5 females; 3 pediatric patients, mean age 10 years, range 5 to 13 years and 9 adult patients, mean age 50.6 years, range 35 to 63 years) underwent fluorescein-guided surgery. No side effects related to SF occurred. In all tumors, contrast enhancement on preoperative MRI correlated with intense, heterogeneous yellow fluorescence with bright fluorescent cystic fluid. Fluorescein was considered helpful in distinguishing tumors from viable tissue in all cases. Gross total resection was achieved in 8 cases (66.7%); in 4 cases, otherwise, the resection was subtotal with fluorescent residual spots to avoid neurological worsening (33.3%). Conclusions The use of SF is a valuable method for safe fluorescence-guided tumor resection. Our data documented a positive effect of fluorescein-guided surgery on intraoperative visualization, suggesting a probable role in improving the extent of resection during yellow surgery of PXA.